A Step Towards Digital Museum - Devinta Nur Arumsari; Virginia Mandasari; Muhadjir Anwar; Dominikus Aditya Fitriyanto; Hery Pudjoprastiono (Nusantara Science and Technology Proceedings, 2022)
The existence of the Covid-19 pandemic has become a catalyst for the increasingly widespread use of digital technology, particularly in the tourism industry, which relies on visitors for revenue. Virtual tours and long-distance interactive forms of tourism, such as those found in museums, are examples of the current trend toward digital tourism. Several museums in Indonesia, including the Bandung Geological Museum, have entered the digitalization stage by offering virtual tours and edutainment. This research aims to provide insight into digital transformation in the tourism sector, particularly museums. This study discovered that curators should create websites that use communication strategies related to their collections and focus on visitor profiles.